Effects of Stocking Density on the Production of Nile Tilapia (Oreochromis niloticus) in Floating Net Cages on the Volta Lake - Asase, A. (University of Ghana, 2013)
Stocking density is an important factor affecting fish production in cages. However, information related to its impact on the growth performance of Nile tilapia Oreochromis niloticus fingerlings during cage culture under the ecological conditions of the Volta Lake in Ghana is limited. Hence, healthy Oreochromis niloticus fingerlings (2.12 ± 0.02 g) were randomly stocked in triplicate 8 m 3 cages at densities of 50 fish/m 3 , 100 fish/m 3 and 150 fish/m 3 and fed a commercially extruded diet (30% Crude Protein) to evaluate their growth and economic feasibility. After 177 days of culture, differences in growth (weight gain and final weights) at these densities were significant (p < 0.05). Fish stocked at 50 fish /m 3 exhibited the highest average weight gain (271.98 ± 0.39 g) while fish stocked at 150 fish/ m 3 had the lowest (169.15 ± 0.49 g). There were significant effects (p < 0.05) of stocking density on daily weight gain, specific growth rate and survival rates. Moreover, the feed conversion ratio and protein efficiency ratio were significantly affected by stocking densities (p < 0.05). However, differences in daily weight gain, specific growth rates, condition factor and profit index were not significant (p > 0.05) between the 100 fish/m 3 and 150 fish/m 3 treatments. The production (10.697 - 22.48 kg/m 3 ), net yield (84.55 – 177.25 kg/cage) and gross profits (GH₵ 63.73 – 229.8) showed significant (p < 0.05) increase with higher stocking densities. Apart from dissolved oxygen which declined below optimal concentrations in February 2012, the levels of water quality parameters measured remained within suitable ranges for Nile tilapia growth throughout the experiment. The study demonstrated that cage farmers can utilize stocking densities of 50 fish/m 3 and 150 fish/m 3 effectively for larger size demand over a six months period and augmented production respectively.
Thesis (MPHIL) - University of Ghana, 2013